Combination of Trace Metal to Improve Solventogenesis of Clostridium carboxidivorans P7 in Syngas Fermentation - Han, Yi-Fan; Xie, Bin-Tao; Wu, Guang-xun; Guo, Ya-Qiong; Li, De-Mao; Huang, Zhi-Yong (Frontiers in Microbiology, 2020)
Higher alcohols such as butanol (C4 alcohol) and hexanol (C6 alcohol) are superior biofuels compared to ethanol. Clostridium carboxidivorans P7 is a typical acetogen capable of producing C4 and C6 alcohols natively. In this study, the composition of trace metals in culture medium was adjusted, and the effects of these adjustments on artificial syngas fermentation by C. carboxidivorans P7 were investigated. Nickel and ferrous ions were essential for growth and metabolite synthesis during syngas fermentation by P7. However, a decreased dose of molybdate improved alcohol fermentation performance by stimulating carbon fixation and solventogenesis. In response to the modified trace metal composition, cells grew to a maximum OD600nm of 1.6 and accumulated ethanol and butanol to maximum concentrations of 2.0 and 1.0 g/L, respectively, in serum bottles. These yields were ten-fold higher than the yields generated using the original composition of trace metals. Furthermore, 0.5 g/L of hexanol was detected at the end of fermentation. The results from gene expression experiments examining genes related to carbon fixation and organic acid and solvent synthesis pathways revealed a dramatic up-regulation of the Wood-Ljungdahl pathway (WLP) gene cluster, the bcs gene cluster, and a putative CoA transferase and butanol dehydrogenase, thereby indicating that both de novo synthesis and acid re-assimilation contributed to the significantly elevated accumulation of higher alcohols. The bdh35 gene was speculated to be the key target for butanol synthesis during solventogenesis.